The Epistemology of Inclusive Education in Islamic Education: Reconstructing The Role of The Teacher as a Murabbi For Children With Special Needs - Amelia Amelia; Fifi Ariska; Samsinar Syarifuddin (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study addresses the persistent fragmentation between general inclusive education frameworks and authentic Islamic pedagogical traditions by constructing a coherent epistemological model for special needs schooling. Utilizing a qualitative conceptual analysis combined with a hermeneutic approach, the research systematically synthesizes foundational primary sources with contemporary pedagogical literature, policy frameworks, and special education paradigms. The analysis establishes that Islamic education possesses a robust epistemological foundation rooted in human dignity, justice, compassion, and universal knowledge acquisition. To operationalize these principles, the paper reconstructs teacher identity from a conventional knowledge transmitter toward a holistic educator across spiritual, intellectual, emotional, and social dimensions, replacing deficit models with strength based approaches. Furthermore, the conceptual framework demonstrates that sustainable implementation depends on institutional governance reform, special education teacher integration, and participatory community ecosystems. By aligning foundational principles with structural school management, this research provides a transferable conceptual model that transforms inclusive Islamic education from an administrative obligation into an epistemologically grounded, sustainable reality for learners with special needs.